2020
DOI: 10.1111/dom.14105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes mellitus on the severity and fatality of SARS‐CoV‐2 (COVID‐19) infection

Abstract: Aim To evaluate the influence of diabetes on the severity and fatality of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection. Materials and Methods The medical records of 66 hospitalized coronavirus disease 2019 (COVID‐19) patients were collected and classified into non‐severe (mild/moderate cases) and severe (severe/critical cases) groups. Logistic regression analysis was used to estimate the risk of severe COVID‐19 (severe/critical infection). In addition, a meta‐analysis including publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 45 publications
5
97
0
2
Order By: Relevance
“…Independent risk factors associated with severe COVID-19 include male sex, increased age, and presence of comorbidities [ 6 , [8] , [9] , [10] , [36] , [37] , [38] ]. To evaluate whether the spatial distribution and abundance of ACE2 protein in the lower respiratory tract differed by these risk factors, we scored tissues for ACE2 protein detection ( Supplemental Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Independent risk factors associated with severe COVID-19 include male sex, increased age, and presence of comorbidities [ 6 , [8] , [9] , [10] , [36] , [37] , [38] ]. To evaluate whether the spatial distribution and abundance of ACE2 protein in the lower respiratory tract differed by these risk factors, we scored tissues for ACE2 protein detection ( Supplemental Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…2) Control group was defined as lacking these chronic comorbidities and lacking clinical lung disease. The definition of chronic comorbidities was informed by reported independent risk factors for mortality in COVID-19 [8] , [9] , [10] . The cumulative cohort included 29 cases (15 chronic comorbidities and 14 controls) with a broad range of ages (0•5 – 71 years) and both sexes were represented (13 female and 16 male).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies and meta-analyses have shown that patients with diabetes have a significantly higher risk of severe COVID-19 and increased mortality rates [14][15][16], A c c e p t e d M a n u s c r i p t the impact of hyperglycemia itself, rather than the presence of DM, has not been sufficiently described in non-critically patients hospitalized with COVID-19.…”
Section: Hyperglycemia Upregulates Ace2 Expression and Induces Glycosmentioning
confidence: 99%
“…SARS-CoV-2 is the etiologic agent of coronavirus disease 2019 (COVID- 19) which was first recognized in December 2019 and has now reached pandemic proportions (2,4). SARS-CoV-2 infection can be fatal, with the risk for increased disease severity correlating with advanced age and underlying comorbidities, while children and younger individuals generally have milder disease (5)(6)(7)(8)(9)(10)(11). These trends in disease severity could reflect differences in ACE2 distribution and expression in the respiratory tract.…”
Section: Introductionmentioning
confidence: 99%